An Annotated Draft Genome of the Mountain Hare (Lepus timidus). (13th December 2019) - Marques, João P; Seixas, Fernando A; Farelo, Liliana; Callahan, Colin M; Good, Jeffrey M; Montgomery, W Ian; Reid, Neil; Alves, Paulo C; Boursot, Pierre; Melo-Ferreira, José
Abstract: Hares (genus Lepus ) provide clear examples of repeated and often massive introgressive hybridization and striking local adaptations. Genomic studies on this group have so far relied on comparisons to the European rabbit ( Oryctolagus cuniculus ) reference genome. Here, we report the first de novo draft reference genome for a hare species, the mountain hare ( Lepus timidus ), and evaluate the efficacy of whole-genome re-sequencing analyses using the new reference versus using the rabbit reference genome. The genome was assembled using the ALLPATHS-LG protocol with a combination of overlapping pair and mate-pair Illumina sequencing (77x coverage). The assembly contained 32, 294 scaffolds with a total length of 2.7 Gb and a scaffold N50 of 3.4 Mb. Re-scaffolding based on the rabbit reference reduced the total number of scaffolds to 4, 205 with a scaffold N50 of 194 Mb. A correspondence was found between 22 of these hare scaffolds and the rabbit chromosomes, based on gene content and direct alignment. We annotated 24, 578 protein coding genes by combining ab-initio predictions, homology search, and transcriptome data, of which 683 were solely derived from hare-specific transcriptome data. The hare reference genome is therefore a new resource to discover and investigate hare-specific variation. Similar estimates of heterozygosity and inferred demographic history profiles were obtained when mapping hare whole-genome re-sequencing data to the new hare draft genome or to alternative references based on the rabbit genome. Our results validate previous reference-based strategies and suggest that the chromosome-scale hare draft genome should enable chromosome-wide analyses and genome scans on hares.